Management matters - Gould, Rebecca A.; Canter, Deborah D. (My University, 2009)
Fewer than 50% of registered dietitians (RDs) supervise personnel and 76% have no budget authority. Because higher salaries are tied to increasing levels of authority and responsibility, RDs must seek management and leadership roles to enjoy the increased remuneration tied to such positions. Advanced-level practice in any area of dietetics demands powerful communication abilities, proficiency in budgeting and finance, comfort with technology, higher-order decision-making/problem-solving skills, and well-honed human resource management capabilities, all foundational to competent management practice. As RDs envision the future of the dietetics profession, practitioners must evaluate management competence in both hard and soft skills. Just as research is needed to support evidence-based clinical practice, the same is needed to support management practice across the profession. Dietetics educators and preceptors should be as enthusiastic about management practice as they are clinical practice when educating and mentoring future professionals. Such encouragement and support can mean that new RDs and dietetic technicians, registered, will understand what it takes to advance to higher levels of responsibility, authority, and subsequent enhanced remuneration. In the ever-changing social, legal, ethical, political, economic, technological, and ecological environments of work, food and nutrition professionals who are willing to step forward and assume the risks and responsibilities of management also will share in the rewards, and propel the profession to new heights of recognition and respect.
Keywords: Management; Dietetics; Remuneration; Compensation; Responsibility; Risk